Can standardized pathology examination increase the lymph node yield following laparoscopic distal pancreatectomy for ductal adenocarcinoma?. Issue 2 (February 2018) - Sahakyan, Mushegh A.; Haugvik, Sven P.; Røsok, Bård I.; Kazaryan, Airazat M.; Ignjatovic, Dejan; Buanes, Trond; Labori, Knut J.; Verbeke, Caroline S.; Edwin, Bjørn
Abstract: Background: Lymph node yield (LNY) is an indicator of oncological adequacy of surgery in patients with pancreatic ductal adenocarcinoma (PDAC). Our hypothesis is that standardized pathology examination (SPE) aimed at accurate staging can increase the LNY without changing surgical technique. Methods: After the introduction of SPE for distal pancreatosplenectomy specimens at Oslo University Hospital, prospective data were collected on patients with PDAC undergoing laparoscopic distal pancreatosplenectomy (LDP). Their data were compared with retrospective data from specimens examined in a non-standardized way (NSPE). Results: SPE and NSPE were applied to 20 and 33 specimens, respectively. SPE was associated with a higher LNY and a higher median number of positive lymph nodes (PLN) in the specimen (18 vs 7, P = 0.001 and 4 vs 1, P = 0.005, respectively). In the stepwise regression model, SPE and younger age resulted in an increased LNY. In the logistic regression model, increased LNY and larger tumor size positively correlated with the presence of PLN. Conclusion: SPE of distal pancreatosplenectomy specimens is associated with higher LNY in patients with PDAC, which increases the likelihood of detecting PLN and reduces the risk of understaging. These findings also indicate that the LDP technique provides an adequate LNY in patients with PDAC.